Exploratory Study: How Students in Multicultural Environment Display Collaboration Skills through Jigsaw Model Implementation in Primary Years - Pitaloka, Yushal Anggia; Neolaka, Grace Amialia Anfetonanda (Universitas Muhammadiyah Mataram, 2023)
With the increasing globalization of society, classrooms environments are becoming more diverse, incorporating students from various cultural backgrounds. This diversity holds the potential for inclusive learning environments that embrace the differences among school members. However, such differences can give rise to communication problems, misunderstandings, divergent expectations, and lack of tolerance towards diversity. Prior studies have explored the effectiveness of collaborative learning in fostering collaboration and teamwork among students from diverse cultural backgrounds. Nevertheless, the specific discussion of collaboration skills among students in Indonesian multicultural schools remains unclear. Hence, this study aims to investigate how students in Indonesian multicultural schools exhibit their collaboration skills through the utilization of the jigsaw learning model. Qualitative methods, including classroom observation and semi-structured interviews, were employed to collect data for this study. The findings indicate that students in multicultural schools effectively overcome challenges stemming from cultural differences and demonstrate positive collaborative behaviors when implementing the jigsaw learning method. These behaviors include interactive communication, respect for differing opinions, resource sharing, group identification, and a focus on achieving shared goals. However, a minority of students encountered difficulties in sharing resources due to personal factors. The study concludes with recommendations for future research endeavors in this field.